Present trans‐Pacific disjunct distribution of Aristolochia subgenus Isotrema (Aristolochiaceae) was shaped by dispersal, vicariance and extinction. (27th August 2013) - González, Favio; Wagner, Sarah T.; Salomo, Karsten; Symmank, Lars; Samain, Marie‐Stéphanie; Isnard, Sandrine; Rowe, Nick P.; Neinhuis, Christoph; Wanke, Stefan; Carine, Mark
Abstract Aim Isotrema is a monophyletic subgenus of Aristolochia with species in East Asia and North/Central America. Earlier studies, based on limited sampling, suggested that the Asian and American species do not form two reciprocal sister clades. We reconstructed phylogenetic relationships within Isotrema to infer the biogeographical events that have shaped its present‐day distribution. Location Eastern Asia, North America, Mexico, Central America. Methods We performed parsimony and Bayesian phylogenetic analyses of 54 accessions using three chloroplast regions. The temporal origins were traced with relaxed phylogenetics and penalized likelihood using fossil calibrations; these methods were combined with ancestral area reconstructions in a comparative approach using statistical dispersal–vicariance analysis (S‐DIVA) and dispersal–extinction–cladogenesis (DEC) analyses. Results The ancestors of the herbaceous eastern North American species and the woody species probably diverged during the Oligocene. The woody species form a Neotropical and a North American/Eastern Asian clade. Diversification in the Neotropical and North American/Eastern Asian clades occurred mostly in the Miocene. In the latter clade, two further intercontinental splits are reconstructed: between the exclusively western North American Aristolochia californica and most of the Asian taxa, and between A. manshuriensis and A. tomentosa. Main conclusions The present distribution of Isotrema developed via a number of dispersal, vicariance and extinction events. The disjunct distributions observed may be the result mainly of non‐synchronous events (e.g. a decrease of mean annual temperature in the Oligocene and the development of unfavourable conditions across the Bering land bridge) that were responsible for the fragmentation of the mesophytic forests. Later diversifications may be correlated with events such as the orogeny of the Western Cordillera and Appalachian Mountains, the development of extensive grasslands in North America, and the mainland extension of Central America southwards to western and central Panama.